ALTERNATIVE DESPUTE RESOLUTION DALAM SENGKETA BISNIS ISLAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Ahmad Hasan Basri; Rozatul Muna; Mahrus Alwi Hasan Siregar (Institut Agama Islam Ngawi, 2021)
Abstract Sharia business dispute is a form of civil dispute. In the settlement of civil disputes, the settlement can be done through litigation and non-litigation. One form of non-litigation dispute resolution is the Alternative Despute Resolution. This research is a qualitative research and uses a normative juridical approach. In this study, the formulation of the problem is about how the Alternative Despute Resolution according to positive law and Islamic law. In positive law Alternative Despute Resolution is accommodated in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. In Alternative Despute Resolution, Islam is also familiar with islah. Etymologically, Islah means to decide disputes. The terminology can be interpreted as a contract agreement made to resolve a dispute. In resolving disputes in Indonesia in the field of sharia economics or sharia business, it can be done with Alternative Despute Resolution. Because almost all contracts contained in the MUI DSN Fatwa require that if one party does not fulfill its obligations or if there is a dispute between the two parties, then the settlement is carried out through the Sharia Arbitration Board after no agreement is reached through deliberation. Keyword : Alternative Despute Resolution, Positive Law, Islamic Law